Gender neutrality improved completion rate for all. Issue 2 (2nd July 2016) - Svedin, Maria; Bälter, Olle
ABSTRACT: The purpose of the present study was to investigate if we could improve retention by redesigning an online programming course from a gender perspective, while maintaining the focus on preferable and sustainable learning approaches. The study builds on results from an earlier study that investigated the relationship between approaches to learning and course completion and involves 1067 students that responded to the short version of the Approaches and Study Skills Inventory for Students (ASSIST) in 2010, 2012 and 2013. Three principles for course material design were identified; gender neutral and non - biased messages, emphasize the interdisciplinary approach and link to everyday examples . Responses to ASSIST were analysed in relation to performed changes in the course literature from a gender perspective. The probability to complete the course increased with 7% points for all students, in particular for men, and decreased for students with a high score in surface approach to learning, especially among women.